Biomechanical in vitro examination of a standardized low-volume tubular femoroplasty. (December 2020) - Horbach, Andreas J.; Staat, Manfred; Pérez-Viana, Daniel; Simmen, Hans-Peter; Neuhaus, Valentin; Pape, Hans-Christoph; Prescher, Andreas; Ciritsis, Bernhard
Abstract: Background: Osteoporosis is associated with the risk of fractures near the hip. Age and comorbidities increase the perioperative risk. Due to the ageing population, fracture of the proximal femur also proves to be a socio-economic problem. Preventive surgical measures have hardly been used so far. Methods: 10 pairs of human femora from fresh cadavers were divided into control and low-volume femoroplasty groups and subjected to a Hayes fall-loading fracture test. The results of the respective localization and classification of the fracture site, the Singh index determined by computed tomography (CT) examination and the parameters in terms of fracture force, work to fracture and stiffness were evaluated statistically and with the finite element method. In addition, a finite element parametric study with different position angles and variants of the tubular geometry of the femoroplasty was performed. Findings: Compared to the control group, the work to fracture could be increased by 33.2%. The fracture force increased by 19.9%. The used technique and instrumentation proved to be standardized and reproducible with an average poly(methyl methacrylate) volume of 10.5 ml. The parametric study showed the best results for the selected angle and geometry. Interpretation: The cadaver studies demonstrated the biomechanical efficacy of the low-volume tubular femoroplasty. The numerical calculations confirmed the optimal choice of positioning as well as the inner and outer diameter of the tube in this setting. The standardized minimally invasive technique with the instruments developed for it could be used in further comparative studies to confirm the measured biomechanical results. Highlights: In patients with osteoporosis, there is an increased risk of fractures near the hip. Patients have an increased perioperative risk due to their age and comorbidities Costs and burdens are out of proportion to the currently used fracture prevention. Standard low volume tubular femoroplasty increase strength of osteoporotic femora Finite element analyses can be used for choosing size and position of femoroplasty.